The Digital Condition Class and Culture in the Information Network - Wilkie, Rob (Fordham University Press, 2011)
The acceleration in science, technology, communication, and production that began in the second half of the twentieth century- developments which make up the concept of the "digital"-has brought us to what might be the most contradictory moment in human history. The digital revolution has made it possible not only to imagine but to actually realize a world in which social inequality and poverty are vanquished. But instead these developments have led to an unprecedented level of accumulation of private profits. Rather than the end of social inequality we are witness to its global expansion. In The Digital Condition, Rob Wilkie advances a groundbreaking analysis of digital culture which argues that the digital geist-which has its genealogy in such concepts as the "body without organs," "spectrality," and "différance"-has obscured the implications of class difference with the phantom of a digital divide.